Profil Kesalahan Konseptual dan Prosedural Mahasiswa STKIP Paris Barantai dalam Menyelesaikan Soal Geometri Analitik Datar - Hartini Hartini (STKIP Paris Barantai, 2020)
The purpose of this study is to describe (1) conceptual and procedural errors in solving mathematical problems related to parabola and hyperbole in STKIP Paris Barantai Kotabaru semester III students in the 2019/2010 school year; (2) the causes of conceptual and procedural errors in solving mathematical problems related to parabola and hyperbole in the third semester students of STKIP Paris Barantai Kotabaru in the academic year 2019/2010. This research is categorized into qualitative research with a descriptive-explorative approach. Data collection techniques through the provision of diagnostic tests and through interviews. The research subjects consisted of 6 (six) people, who were divided into 3 (three) categories namely, 2 (two) low-ability students, 2 (two) medium-ability students, and 2 (two) high-ability students. The results showed that: 1) Conceptual errors that occur in low category subjects were wrong in the agreed concept, and were not quite right in using the formula or theorem in solving a problem; 2) Procedural errors occur in middle category subjects and low category subjects; 3) Concept and procedural errors (occur) occur in low category subjects, namely a) errors using formulas, b) irregularities in the steps to solve problems, and c) student errors in observing and looking for clues. Keywords: Profile, Procedural Error, Conceptual Error, Flat Alitic Geometry.